Data for numerical examples in "Generative Benchmark Models for Mesoscale Structure in Multilayer Networks" - Bazzi, M; Jeub, L (University of Oxford, 2016)
This package includes the raw data used to generate the plots in Figures 8-10 of "Generative benchmark models for mesoscale structure in multilayer networks", by M. Bazzi, L. G. S. Jeub, A. Arenas, S. D. Howison, and M. A. Porter, arXiv:1608.06196. It was created using MATLAB and all variables are stored in .mat format. Please see the "Readme.txt" file for additional information on the data set.